COHESIVE DEVICES IN DISCUSSION TEXT WRITTEN BY THE STUDENTS OF SMAN 12 PADANG - Reni Astanti; Yenni Rozimela; Fitrawati Fitrawati (Universitas Negeri Padang, 2016)
The purpose of this research is to analyze the use of cohesive devices in discussion text written by the students of SMAN 12 Padang.. This research is a descriptive qualitative research. This research is conducted on the second grade students of SMAN 12 Padang. There are 20 piece of paper of writing test as the data of this research. Out of 20 these, there are 29 transitional signal used appropriately, and 35 others used inappropriately. Then, there are 35 repetition of key words/nouns used appropriately, and 36 others used inappropriately. The last, there are 44 pronouns used appropriately, and 21 others used inappropriately.